Born from below: Urban regeneration through incarnational theological formation in Guatemala City and beyond - Ribbens, Michael L. (HTS teologiese studies, 2018)
This article sets out to describe the development of and engagement with a global training collaborative around the formation of urban ministry leadership committed to the act of loving cities and working for peace. The collaborative is an initiative of Street Psalms called the Urban Training Collaborative and each urban training hub has agreed to be shaped and formed by an Incarnational Training Framework (ITF). The ITF was constructed over a 20-year period in the midst of a global missional community made up of leaders from cities all over the world. The ITF is infused by an incarnational theology as interpreted from below and focused on the message, method and manner as exemplified in the life and mission of Jesus Christ such that messengers are free of fear and unleashed to love their cities and seek their peace. The Incarnation of Jesus Christ animates faith-based engagement around the complex issues of poverty, injustice, social inequity and violence, and shifts paradigms from scarcity to abundance, theory to practice and rivalry to peacemaking. To shed light on the practical outworking of an incarnational theology from below, we will critically reflect on Guatemala City as a case study to illustrate how the formation of a city-wide missional community was developed through engagement around the aforementioned ITF which led to the corresponding paradigm shifts and then subsequently seeding a global training collaborative